The Effect of Sprint Interval Training on Hippocampal Nerve Growth Factor and Cognitive Performance in Male Wistar Rats - Elham Azizi; Esmail Nasiri; Maryam Khalesi (University of Tehran, 2022)
Introduction: Sports activities can protect the brain and improve its function. However, the lack of time is one of the primary reasons for not participating in the recommended amount of sports activities. Therefore, the present study aimed to investigate the effects of sprint interval training (SIT) on hippocampal nerve growth factor (NGF) levels, learning, and spatial memory in adult male rats.Methods: For this, 16 male Wistar rats were divided into two equal groups (control and SIT). The SIT protocol consisted of eight weeks of running on the treadmill (three sessions per week, 4-9 repetitions of 10 seconds sprints, and 1 min rest between repetitions). At the end of the eighth week, the rats' cognitive performance was evaluated using the shuttle box and Y-maze avoidance tests. Finally, rats were anesthetized and the hippocampus was removed and NGF levels were measured.Results: The findings showed that in the SIT group, the hippocampal NGF levels were significantly higher than the control group (p=0.001). Moreover, rats in the SIT group had better performance in the shuttle box and Y-maze avoidance tests than the control group, but the difference between groups was not statistically significant (p>0.05).Conclusion: Based on the findings of the present study, it seems that SIT (with 10 seconds repetitions) can increase the hippocampal NGF levels, though, to improve our knowledge about its effect on cognitive performance, more studies are needed